Reactive Extraction of L (+) Tartaric Acid by Amberlite LA-2 in Different Solvents - I. Inci; Y. S. Asçi; A. F. Tuyun (E-Journal of Chemistry)
The extraction of L(+) tartaric acid from aqueous solutions by amberlite LA-2 is a secondary amine mixture in different diluent solvents. Extraction equilibria of L(+) tartaric acid by amberlite LA-2 in 1-octanol, cyclohexane, isooctane, hexane, methyl isobutyl ketone (MIBK) solvents at temperature 298.15 K have been measured. The batch extraction experiments distribution coefficients (D), loading factors ( Z) and extraction efficiency (E) were calculated. The maximum removal of L(+) tartaric acid is 91 % with MIBK and 0.92 mol.L-1 initial concentration of Amberlite LA-2.